U.S. trends in elective and emergent major abdominal surgical procedures from 2002 to 2014 in older adults. Issue 8 (10th May 2021) - Rubin, Daniel S.; Huisingh‐Scheetz, Megan; Ferguson, Mark K.; Nagele, Peter; Peden, Carol J.; Lauderdale, Diane S.
Abstract: Background: The U.S. population is aging and projected to undergo an increasing number of general surgical procedures. However, recent trends in the frequency of major abdominal procedures in older adults are currently unknown as improvements in non‐operative interventions may obviate the need for major surgery. Thus, we evaluated the trends of major abdominal surgical procedures in older adults in the United States. Methods: We performed a retrospective cohort study using the National Inpatient Sample from 2002 to 2014 with trend analysis using National Cancer Institute's Joinpoint Trend Analysis Software. We identified the average annual percent change (AAPC) in the yearly frequency of major abdominal surgical procedures in older adults (≥50 years of age). Results: Our cohort included a total of 3, 951, 947 survey‐weighted discharges that included a major abdominal surgery in adults ≥50 years of age between 2002 and 2014. Of these discharges, 2, 529, 507 (64.0%) were for elective abdominal surgeries, 2, 062, 835 (52.0%) were for female patients, and mean (SD) age was 61.4 (15.9) years. The frequency of major abdominal procedures (elective and emergent) decreased for adults aged 65–74 (AAPC: −1.43, −1.75, −1.11, p < 0.0001), 75–84 (AAPC: −2.75, −3.33, −2.16, p < 0.001), and ≥85 (AAPC: −4.07, −4.67, −3.47, p < 0.0001). The AAPC for elective procedures decreased for older adults aged 75–84 (AAPC = −1.65; −2.44, −0.85: p = 0.0001) and >85 (AAPC = −3.53; −4.57, −2.48: p < 0.0001). All age groups showed decreases in emergent procedures in 50–64 (AAPC = −1.76, −2.00, −1.52, p < 0.0001), 65–74 (AAPC = −3.59, −4.03, −3.14, p < 0.0001), 75–84 (AAPC = −3.90, −4.34, −3.46, p < 0.0001), ≥85 (AAPC = −4.58, −4.98, −4.17, p < 0.0001) age groups. Conclusions and Relevance: In this cohort of older adults, the frequency of emergent and elective major abdominal procedures in adults ≥65 years of age decreased with significant variation among individual procedure types. Future studies are needed to identify the generalizability of our findings to other surgical procedures.